Perinatal depressive and anxiety symptoms are associated with gut microbiota in pregnant women with overweight and obesity - Hieta, Janina; Benchraka, Chouaib; Pärnänen, Katariina; Houttu, Noora; Mokkala, Kati; Lotankar, Mrunalini; Kataja, Eeva-Leena; Lahti, Leo; Laitinen, Kirsi (ELSEVIER, 2025)
The associations of gut microbiota with depressive and anxiety symptoms have been investigated mainly in non-pregnant humans, and currently there is a significant gap in research on pregnant women, especially those who are living with overweight and thus at a higher risk for experiencing perinatal mental health problems. In this study, we used shotgun metagenomic sequencing to analyze the gut microbiota of pregnant women with overweight and obesity, both in early and late pregnancy. We compared gut microbial diversity, composition, and function across groups with different trajectories of depressive (n=419) and anxiety (n=408) symptoms. Depressive symptoms were assessed using the Edinburgh Postnatal Depression Scale (EPDS), and anxiety symptoms were evaluated with the Symptom Checklist 90 (SCL-90, anxiety subscale) at five time points spanning from early pregnancy to one year postpartum. Latent growth mixture modeling (LGMM) was used to model symptom trajectories from early pregnancy until one year postpartum and further symptom sum scores at five time points cross-sectionally. We observed differences in several bacterial species abundances between the trajectory groups and in cross-sectional analyses, including higher abundance of Hungatella hathewayi in the Moderate and increasing depressive symptoms group (FDR<0.25), and Bacteroides clarus in the High and decreasing depressive symptoms group (FDR<0.25) and in women experiencing clinically significant postpartum anxiety symptoms (FDR<0.05). No differences were found regarding the gut microbiota diversity (alpha or beta) or function. The results suggest that maternal gut microbiota, particularly the increased abundance of possible pro-inflammatory species, could be one of the factors affecting perinatal distress.